2019
DOI: 10.1200/jco.2019.37.15_suppl.e17119
|View full text |Cite
|
Sign up to set email alerts
|

Universal endometrial cancer tumor typing: How much has immunohistochemistry, microsatellite instability, and MLH1 methylation improved the diagnosis of Lynch syndrome across the population?

Abstract: e17119 Background: Universal tumor testing for defective DNA mismatch repair (MMR) is recommended for all women diagnosed with endometrial cancer (EC) to identify those with underlying Lynch syndrome (LS). However, since its implementation in 2013, the effectiveness of this screening method on identifying individuals with LS across the population has not been well studied. The aim of this study was to evaluate outcomes of MMR immunohistochemistry (IHC), MLH1 methylation, and microsatellite instability (MSI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…MSH2 expression in one cervical precursor lesion and in one urothelial carcinoma of the urinary bladder could be explained by the oncogenic role of human papillomavirus and tobacco as potent carcinogens in the cervix and urothelial epithelium [ 20 , 21 ]. In the two endometrial MSH2-positive cancers, the remaining MMR proteins were also expressed, although the PCR microsatellite instability analysis results were unstable (data not shown), consistent with results previously reported [ 22 , 23 ]. In the two breast lesions, other carcinogenetic pathways different from the MMR system may be activated [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…MSH2 expression in one cervical precursor lesion and in one urothelial carcinoma of the urinary bladder could be explained by the oncogenic role of human papillomavirus and tobacco as potent carcinogens in the cervix and urothelial epithelium [ 20 , 21 ]. In the two endometrial MSH2-positive cancers, the remaining MMR proteins were also expressed, although the PCR microsatellite instability analysis results were unstable (data not shown), consistent with results previously reported [ 22 , 23 ]. In the two breast lesions, other carcinogenetic pathways different from the MMR system may be activated [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Over a quarter of our study patients (28%) had tumor mismatch repair deficiency which is similar to rates reported in the literature (6). While none were found to have a pathogenic mutation in MMR proteins associated with Lynch syndrome, several VUS were discovered in MMR proteins.…”
Section: Methodssupporting
confidence: 88%
“…Information about mismatch repair deficiency even in the absence of a germline mutation has clinical implications including eligibility for targeted therapy for recurrent mismatch repair-deficient tumors. While mismatch repair status was initially found to predict clinical benefit of a PD-1 blockade in patients with colorectal cancer, subsequent studies then demonstrated response in other solid tumors as well, including endometrial cancer, where mismatch repair deficiency is found in up to 30% of tumors (6,17,18). Since the Food and Drug Administration (FDA) approval in 2017, PD-1 blockade with pembrolizumab has been used in the treatment of mismatch repair-deficient recurrent endometrial cancer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular subtyping of two models with serous histology revealed one was p53wt tumor (PDX23) and another was MMRd (PDX53), which was consistent with a germline MSH6 mutation (p.Tyr214*) in the latter patient and the finding that 13% of patients with germline MMR mutations have a mixed serous histology (32). Somatic mutations detected in other genes were consistent with TCGA findings.…”
Section: Genomics Of Ec Pdx Modelssupporting
confidence: 74%